26 feet divided by 15/2 inches
26 * 12 = 312
312 * 2/15
624/15
41 9/15
41 3/5
she can make 41 bracelets
The standard form of the quadratic function f(x) = -3x^2 + 6x - 2 is f(x) = -3x^2 + 6x - 2
<h3>How to represent the
quadratic function in standard form?</h3>
The quadratic function is given as
f(x) = -3x^2 + 6x - 2
The standard form of a quadratic function is represented as:
f(x) = ax^2 + bx + c
When both equations are compared, we can see that the function f(x) = -3x^2 + 6x - 2 is already in standard form
Where
a = -3
b = 6
c = -2
Hence, the standard form of the quadratic function f(x) = -3x^2 + 6x - 2 is f(x) = -3x^2 + 6x - 2
Read more about quadratic function at
brainly.com/question/25841119
#SPJ1
Y=mx+b
m=slope
b=y intercept
we are given (3,-1)
one solution is x=3 and y=-1 or
when x=3 then y=-1
also slope=2
so
y=2x+b
subsitue 3 for x and -1 for y and solve for b
-1=2(3)+b
-1=6+b
subtract 6
-7=b
y=2x-7 is equation
answer is number 4
Here's one shortcut:
2.3×10^9=1000(2.3×10^6) because your adding 3 more zeros to 2300000
Answer:
629.9
Step-by-step explanation: